Liberal rationality in The Fable of the Bees. A comparison with Adam Smith and Wenceslao Fernández Flórez - Carlos Rodríguez Braun; Fernando Méndez Ibisate (Iberian Journal of the History of Economic Thought)
Mandeville, Smith and Fernández Flórez approached economic and social problems defending liberty and at the same time acknowledging the existence of conflicts and contradictions that demand ethics, politics and law. Their liberal rationality is not Panglossianly optimistic, neither is it cynic, and their individualism not only does not exclude society but builds upon it. They admitted the complexity of human nature and society as they really are, and recognized that we would not progress economically suppressing the market, just as we would not do so morally in a fantastic universe without sins. The three stressed that institutions and rules are indispensable in communities of free and responsible people. They rejected the excesses of power and warned of the dangers of promoting ideal worlds.